The influence of parental age and allelic status of gene white on Drosophila melanogaster fitness - Колот, Н. В.; Костенко, В. В.; Воробйова, Л. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
We have analyzed fitness components (eggs production, level of dominant lethal mutations, fertility, and viability) in the first generation offspring of 3-, 10- and 20-days parents in Drosophila melanogaster wild-type and mutant stocks with different alleles of the locus white. It has been shown that with the increase of parental age in the first generation offspring of all the studied stocks eggs production, fertility, viability decrease and percentage of dominant lethal mutations increase, especially in the early stages of embryogenesis. Formation of studied fitness components of the offspring depends not only on the age of parents, but also on the genetic background and allelic status of the white gene.